Análise do fluxo reverso de pilhas pós-consumo na cidade de João Pessoa - PB - Pinheiro, Aldilene Bezerra (2024)
In recent decades, accelerated technological development, mass consumption and shorter product life cycles have led to an increase in the consumption and disposal of electrical and electronic equipment (EEE). When they reach the end of their useful life, these products become waste electrical and electronic equipment (WEEE). Batteries, which are part of this category of waste, can contain heavy metals which, when disposed of inappropriately, because they contain bioaccumulative elements, cause damage to human health and the environment. With this in mind, this study aims to identify the reverse flow of post-consumer batteries in João Pessoa - PB in order to provide information that will contribute to the reverse logistics system for this waste in the city. To this end, data was collected from a sample of 400 inhabitants, by contacting battery users using an online form; surveying and verifying the activities of the voluntary battery drop-off points (PEVs) registered with Green Eletron; and installing a model PEV, the result of a partnership between the TREE extension project and the Paraíba Data Processing Company (CODATA). Most of the participants in the survey dispose of batteries in ordinary household waste (62.6%), rate the provision of disposal information in establishments as poor (50.5%), and are unaware of the existence of PEVs in the city (67.3%). They have some knowledge of the risks of incorrect disposal and the legal instruments available, but report that the lack of voluntary battery drop-off points would be one of the main difficulties for proper disposal. Of the total, only 20.8% claimed to dispose of batteries at PEVs. Of the PEVs registered, only 19 showed active collection and of these only 13 had a collector in a visible place that was easily accessible to the public. In 210 days of collection at CODATA's PEV, a total of 17.535 kg of post-consumer batteries were obtained, accounting for 1,172 units, representing around 94.36% of the expected amount, with around 0.085 kg per capita. Some of the improvements for the implementation and success of reverse logistics are related to the installation of new PEVs for batteries in strategically located neighborhoods, greater publicity for existing points, environmental awareness activities, and it is possible to think of public policies that invest in some sort of bonus system, serving as an incentive for consumers to dispose of batteries.